CSR disclosure and its impacts on financial performance and institutional ownership : evidence from the Malaysian public listed companies / Mustaruddin - Mustaruddin, Mustaruddin (2009)
The pressure on companies to carry out Corporate Social Responsibility (CSR) efforts has gained impetus in current times, as a way of sustaining a competitive advantage in business. Previous studies found that the awareness and involvement of Public Listed Companies (PLCs) in Malaysia in practicing CSR activities were high; however, the level of disclosure of such activities is relatively low. The aim of this thesis is to explore CSR disclosure (CSRD) and its relation to Corporate Financial Performance (CFP) and Institutional Ownership (IO) of the Malaysian PLCs. In this thesis, a longitudinal study of 200 highest market capitalizations sampled from 474 companies listed on the main-board of Bursa Malaysia during the period 1999 to 2005 is conducted. This study employs robust regression methods, namely, the Generalized Least Squares (GLS) with Fixed Effect Model (FEM). The findings reveal that CSRD in the annual reports of PLCs in Malaysia is at its emerging stages, where the involvement of the Malaysian PLCs in CSR practices is improving. The number of companies disclosing their CSR practices has increased during the seven year period with an average growth of CSRD information at approximately 10.8 percent yearly. The employee relations dimension has the highest disclosure, followed by the community involvement dimension, and finally the product and environment dimensions. It was also found that the three industries with the highest level of disclosure are the plantation, construction and consumer products industries. To observe the statistical power, longitudinal data analysis with a large-sample testing was carried out. Results which confirmed earlier estimations indicated that there are positive and significant relationships between CSRD and CFP as well as IO. Results of the hypotheses testing based on the CSR dimensions also found that all four dimensions are positive and significantly related to CFP. Two of the CSR dimensions namely employee relations and product were found to be positively related to IO, while the community involvement and environment dimensions were negatively related to IO. Lastly, both CSRD and IO support the hypothesis as being positive and significantly related to CFP for PLCs in Malaysia. These results suggest that institutional investors hold their shares for longer time periods when they believed that companies are concerned with socially responsible practices. This proves that CSR practices can be used as a strategic approach to enhance the financial performance and reputation of PLCs in Malaysia. These findings suggest that the Malaysian PLCs should disclose their CSR activities fully, because CSRD has a significant impact in improving CFP and IO in the Malaysian PLCs. The Security Commission should therefore provide a criterion to measure the social performance of companies, such as creating a social performance ranking for PLCs. This ranking could not only set as a benchmark for CSR activities by PLCs in Malaysia, but also be utilized as a general standard measurement to evaluate companies engaging in CSR activities. There are some limitations in the study where the focuses are only on companies‘ annual reports. Future research could consider other media such as stand-alone reporting, in-house magazines, newspapers, and web-sites. Utilizing alternative sampling techniques from a wider population could also improve results as it would assist in making generalised conclusions. Collecting primary data through interviews is also highly recommended, as it would be useful to identify precise motives and perceptions of managers towards the disclosure of CSR activities.